Analysis of The Performance Model of Air Traffic Controllers (ATC) at Airnav Indonesia Balikpapan Branch - Linda Chandler Maramis Sunarto; Amir Fikri; Shine Pintor Siolemba Patiro (PT. Publikasiku Academic Solution, 2023)
As professionals who ensure the safe and efficient operation of air navigation in a specific air space, Air Traffic Controllers (ATC) shall possess maximum performance since their responsibility is related to the safety of many human lives. The purpose of this study is to analyze the factors affecting the behavior of the Air Traffic Controller (ATC) performance model on duty at Airnav Indonesia branch Balikpapan. This research is quantitative and explorative research conducted on all populations of 38 active ATC working in air navigation service provider (ANSP) in Airnav Indonesia Balikpapan for six months from March to August 2022. Data was collected by distributing questionnaires to 38 respondents and conducting 38 interviews. The results demonstrate that Compensation has a positive and significant effect on performance, Competence moderates the relationship between compensation and performance in a positive and significant way, Compensation has a significant positive effect on Employee Engagement, Career Development has a significant positive effect on Employee engagement, Employee engagement has a significant positive effect on performance, and Employee Engagement as a mediating variable that has a significant positive effect on career development and performance. The implications of the findings of this study as a reference for future policy development and human resource development at Airnav Indonesia Balikpapan, in order to improve the quality of air traffic services and flight safety.